Assemblage patterns of hymenoptera at different elevations of Gunung Datuk, Rembau / Noor Nasuha Abd Aziz … [et al.] - Abd Aziz, Noor Nasuha; Mohd Hatta, Siti Khairiyah; Abd Ghani, Idris; Saiyid Shaifuddin, Saiyid Jalaluddin (Research Management Institute (RMI), 2017)
A study on abundance and diversity of Hymenoptera was conducted in Gunung Datuk, Rembau. Samplings were conducted from November 2014 to February 2015 using six Malaise traps. Three traps were placed at Site 1 at 700m height for high elevation and the remaining traps were placed at Site 2 at 200m height for low elevation. A total number of 221 Hymenopteran were collected which consist of nine families namely Ichneumonidae, Formicidae, Braconidae, Bethylidae, Evaniidae, Tiphiidae, Vespidae, Pompilidae and Apidae. In this study, 93 individuals were obtained from Site 1, comprising nine families and 43 morphospecies while 127 individuals were obtained from Site 2 with nine families and 45 morphospecies. Formicidae was the most dominant family collected from both sites with a total of 104 individuals while the least family recorded was Apidae with only one individual. Shannon’s Weiner Diversity Index (H’) showed Site 1 had the higher diversity value with H’ = 3.17 compared to Site 2 with value H’ = 3.12. For Evenness Index, Site 1 had higher value compared to Site 2 with E’ = 0.84 and E’ = 0.82 respectively. Moreover, for Margalef Richness Index, Site 1 recorded R’ = 9.24 while site two recorded R’ = 9.08 which concluded that Site 1 had higher species richness compared to Site 2. Paired t-test showed that both sites had no significant difference with p>0.05. Overall study showed that the diversity and abundance of Hymenoptera in Gunung Datuk were low since the value of H’ is less than 3.50